Altered platelet contents in survivors of early ischemic ventricular fibrillation: Preliminary findings. (February 2014) - De Jong, Jonas S.S.G.; Nieuwland, Rienk; Meijers, Joost C.M.; Korporaal, Suzanne J.; Akkerman, Jan Willem N.; Wilde, Arthur A.A.M.; Dekker, Lukas R.C.
<x xml:space="preserve">Abstract</x> Early ischemic ventricular fibrillation (VF) in the setting of an acute myocardial infarction (AMI) due to thrombotic coronary occlusion remains a major health problem. Several animal studies have shown that platelet-dense granule contents released during thrombus formation can induce arrhythmias. We hypothesize that the platelet release reaction is involved in the predisposition to early ischemic VF. A case-control study was performed in patients who survived VF during a first AMI ("cases, " n = 26) and in patients with one previous AMI without arrhythmias ("controls, " n = 24). All patients were on aspirin 100 mg OD. Baseline platelet activation was assessed with flow cytometry. Response to activation was assessed with aggregometry, flow cytometry and PFA-100 analysis. Differences in platelet contents and content release were assessed by labeling platelet-dense granules with mepacrine and by measuring serotonin and ADP/ATP content. Patient and infarct characteristics and baseline platelet function tests were similar between groups. The mean time from event was 4.9 (±3.2) years among cases and 4.7 (±2.7) years among controls. Dense granule release was similar in cases versus controls. Platelet serotonin content in cases was higher than in controls (611 ± 118 ng/10E9 platelets vs. 536 ± 141 ng/109, p = 0.048). Even years after the event, elevations in the platelet dense granule contents between VF survivors and controls may be detected. These preliminary findings shed new light on the pathophysiological mechanisms underlying ischemic VF, as platelet-dense granules may contain mediators of early ischemic VF risk.